Investigation On Internet Application In Marketing Of Furniture Products By Local Manufacturers - Beng, Lee Chea (2001)
The objective of this study will focus on the surveying of the 300 odd furniture makers on how far they have applied this high technology alternative, namely through the Internet, to solve their marketing problems. The success of the Internet application will then create better opportunity to edge the rivals in international furniture market.